Molecular Characterisation, Attenuation and Inactivation of Very Virulent Infectious Bursal Disease Virus for the Development of Tissue Culture Based-Vaccines - Mohammed, Majed H. (2010)
Infectious bursal disease (IBD), an economically important infectious viral disease of poultry, is caused by IBD virus (IBDV) belonging to Avibirnavirus genus of Birnaviridae family. The disease causes considerable mortality and immunosuppression. Emergence of very virulent IBDV (vvIBDV) strains in different parts of the world in late 1980’s including Malaysia in 1991, have demanded further research efforts in understanding the added complexicity of the disease process and the means to control and prevent outbreaks of the disease. Treatment of IBD is of no value and the disease can only be controlled and prevented by proper vaccination programme and biosecurity. It was the objectives of the study to determine the molecular characteristics and effects of attenuation and inactivation of Malaysian field isolated of vvIBDV for tissue culture based IBD vaccines development. Three IBDV isolates identified as UPM01190, UPM94273 and UPM0081 with an accession number of AY791998, AF527039 and EF208038, respectively were propagated in specific-pathogenic- free (SPF) embryonated chickens egg via chorioallontoic membrane (CAM) for three times and infected onto two types of continuous cell line namely the DF-1and Vero cell lines. The UPM0081 vvIBDV isolate successfully infected these cells while the other vvIBDV isolates failed. The virus was passaged serially 20 and times in Vero cells and DF-1 cell lines, respectively. The cytopathic effects (CPEs) were observed and virus from each passage was confirmed through indirect immunoperoxidase staining test. The UPM0081 was adapted to Vero cells and DF-1 cells line in fourth and third passage, respectively. The molecular characteristics of the virus at different passages in Vero cells and two passages in DF-1 cell line were characterized by using reverse transcriptase polymerase chain reaction (RT-PCR). The nucleotide base sequence of a 643 bp fragment of genome segment A containing the partial coding sequence of VP2 and the entire hyper-variable region were determined. No apparent changes by sequence analysis of selected passage in VP2 gene at passage 5 (UPM0081T5) and passage 7 (UPM0081T7) in Vero cells and DF-1 cell line. One amino acid substitution change occurred in passage 8 (UPM0081T8) and passage 9 (UPM0081T9): 222 (A to P). Further changes in the VP2 gene were recorded in passage 10 (UPM0081T10), passage 15 (UPM0081T15), and passage 20 (UPM0081T20) 222: (A to P), 242 (I to V), 253 (q to H), 256 (I to V), 279: (D to N), 284: (A to T), 294 (I to L), 326 (S to L), and 330 (S to R). Amino acid substitution at positions 279 (D to N) and 284 (A to T) were commonly found in the attenuated IBDV strains. The pathogenicity and immunogenicity properties of the UPM0081 vvIBDV passages 10, 15 and 20 isolutes on Vero cells were evaluated in this study. The results revealed that only UPM0081T10 was still pathogenic to SPF chickens. It caused clinical signs, gross lesions, 25% mortality and histological changes in bursa of Fabricius. Neither clinical signs nor gross lesions were observed in the SPF chickens inoculated with either UPM0081T15 or UPM0081T20. Efficacy test demonstrated that both UPM0081T15 and UPM0081T20 could provide 100% protection in highly susceptible SPF chickens when challenged with vvIBDV (UPM0081) at virus titer or 10 7.8 ELD 50/0.1 mL per chicken. The UPM0081T15 and UPM0081T20 IBDV isolates were inactivated using either Binary ethyleneimine(BEI) or Electrolysed water-Catholyte-Anolyte (ECA). Complete inactivation of UPM0081T15 with titer or 10 6.7 TCID50/0.1 mL and UPM0081T20 with titer of 10 7.4 TCID 50/0.1ml occurred after 24 hours with either BEI or ECA. The inactivated viruse suspension and an equal volume of Freund’s incomplete adjuvant were mixed together (water-in-oil) emulsion and injected subcutaneously into 42-day-old SPF chickens to determine the safety and immunogenicity of the inoculum. Neither clinical signs nor gross lesions were observed in both groups of chickens before and after vvIBDV challenged. High and protective level IBD antibody titer was recorded more in BEI than ECA groups at 2 weeks post infection and 2 weeks post challenged. The study showed that both the inactivated UPM0081T15 either in BEI or ECA was safe and could provide 100% protection against vvIBDV challenged with titer of 10 7.8 EID 50/ 0.1 mL,while that of ECA could not protect fully SPF chicken against bursal lesion. In conclusion, vvIBDV UPM0081 was successfully adapted and attenuated in continous cell line (Vero cells) after fifteen and twenty passages. The attenuated and inactivated local vvIBDV named UPM0081T15 and UPM0081T20 conferred full protection to the immunized SPF chickens against vvIBDV.